Learning curve analysis of transvaginal pelvic reconstruction surgery with four-wing mesh - Huang, Liqiong; Zhang, Jiajia; Xie, Aijie; Li, Xin; Liu, Tianjiao; Wang, Jinbo; Song, Liwen; Chen, Aozheng; Qiu, Jin (Frontiers in Medicine, 2026)
ObjectiveCompared to traditional pelvic reconstruction surgery, transvaginal pelvic reconstruction surgery with four-wing mesh (T4) offers significant advantages in reducing postoperative recurrence rates, improving surgical success, and enhancing patients’ quality of life. However, this procedure requires a high level of expertise from the surgeon, and improper use of the mesh may increase the risk of erosion or displacement. The aim of this study was to analyze the learning curve for T4, providing reference for the further promotion and application of this technique.MethodsA retrospective analysis was conducted on 84 patients with pelvic organ prolapse who underwent the modified T4 procedure between January 2019 and April 2023. Perioperative and follow-up data were collected and compared across different phases of the learning process. The learning curve was plotted using the cumulative sum method, while multiple linear regression analysis was employed to identify factors influencing surgical duration.ResultsAll surgeries were successfully completed without the need for conversion to alternative surgical approaches. The overall mean operative time operative time was 47.80 ± 17.18 min. The learning curve revealed three distinct phases: Phase I (exploratory stage, first 20 cases) with a mean operative time of 65.85 ± 18.04 min, Phase II (competence acquisition stage, the next 49 cases) with a mean OT of 44.33 ± 11.28 min, and Phase III (post-learning phase for the final 15 cases, indicating mastery of the T4 procedure) with a mean operative time of 35.07 ± 13.82 min.ConclusionThe modified T4 procedure demonstrated a three-phase learning curve, with surgical competence appearing to be achieved after approximately 20 cases. Continued experience was associated with improvements in operative efficiency; however, these findings should be interpreted cautiously, as further comparative studies are required to validate the potential clinical advantages of this technique.